Human resource management in marketing recruitment PT. BPRS Aman Syariah in increasing financing productivity - Wahyu Eko Prasetiyo (Digital Business: Tren Bisnis Masa Depan, 2023)
This research is motivated by the existence of recruitment practices that have not yet applied objective views. That is, in conducting recruitment, there are still those who apply subjective principles, which look at the background of the family, relatives and so on, and without regard to the educational background and specific abilities possessed by these Human Resources. Recruitment itself is part of Human Resource Management, which has the goal of meeting the needs of Human Resources in order to be able to fill vacancies in a company, so that there will be no imbalance in the company's future. So that the journey towards the goals desired by the company is more easily achieved. In the recruitment process there are several things that need to be considered, in order to choose the right Human Resources. In The Right Man and The Right Place theory, it is explained that in recruiting and placing Human Resources, one must pay attention to the capabilities of these Human Resources, by looking at their educational background. This research is a field research, using a deductive approach, namely discussing issues from the general to the specific discussion. The data collection model used in this study is observation and interviews. The observation that researchers make is by observing marketing activities in carrying out their work. The interview is to collect other information that cannot be seen empirically. The researcher also compared the recruitment goals with the reality at PT. BPRS Aman Syariah after the recruitment is carried out.